Respostas

2014-01-09T09:08:06-02:00
F(x) = 2x² + 2 + 3x -4

f(0) = 2. 0² + 2 + 3 . 0 - 4
         0 +2 + 0 - 4 =  - 2

f(2) = 2. 2² + 2 + 3 . 2 - 4
        2 . 4 + 2 + 6 - 4
        8 + 8 - 4
         16 - 4 = 12

f( V2) = 2 . V2² + 2 + 3 . V2 - 4
            2 . V4 + 2 + 3 . 1 - 4
            2 . 2 + 2 + 3 - 4
             4 + 2 + 3 - 4
              9 - 4 = 5

f( 1 + V2) = 2 .( 1 + V2)² + 2 + 3 . (1 + V2) - 4
                  2 . ( 1 + 1 )² + 2 + 3 .( 1 + 1) - 4
                    2 . ( 2)² + 2 + 3 . 2 - 4
                    2 . 4 + 2 + 6 - 4
                     8 + 2 + 6 - 4
                      16 - 4 = 12